Pulmonary mitochondrial DNA release and activation of the cGAS-STING pathway in Lethal Stx12 knockout mice - Dan-Hua Liu; Fang Li; Run-Zhou Yang; Zhuanbin Wu; Xiao-Yan Meng; Sen-Miao Li; Wen-Xiu Li; Jia-Kang Li; Dian-Dian Wang; Rui-Yu Wang; Shu-Ang Li; Pei-Pei Liu; et al. (Cell Communication and Signaling)
Abstract STX12 (syntaxin12 or syntaxin13), a member of the SNARE protein family, plays a crucial role in intracellular vesicle transport and membrane fusion. Our previous research demonstrated that Stx12 knockout mice exhibit perinatal lethality with iron deficiency anemia. Despite its importance, the comprehensive physiological and pathological mechanism of STX12 remains largely unknown. Here, we revealed that STX12 deficiency causes the depolarization of mitochondrial membrane potential in zebrafish embryos and mouse embryonic fibroblasts. Additionally, the loss of STX12 decreased the levels of mitochondrial complex subunits, accompanied by mitochondrial DNA (mtDNA) release and activated cGAS-STING pathway and Type I interferon pathway in the lung tissue of Stx12 −/− mice. Additionally, we observed a substantial increase in cytokines and neutrophil infiltration within the lung tissues of Stx12 knockout mice, indicating severe inflammation, which could be a contributing factor for Stx12 −/− mortality. Various interventions have failed to rescue the lethal phenotype, suggesting that systemic effects may contribute to lethality. Further research is warranted to elucidate potential intervention strategies. Overall, our findings uncover the critical role of STX12 in maintaining mitochondrial function and mtDNA stability in pulmonary cells, and reveal that STX12 depletion results in pulmonary mtDNA release and activates mtDNA-dependent innate immunity.